Quantum Error Correction with magnetic molecules. (15th May 2015) - Baldoví, José J.; Cardona-Serra, Salvador; Clemente-Juan, Juan M.; Escalera-Moreno, Luis; Gaita-Ariño, Alejandro; Mínguez Espallargas, Guillermo
Abstract: Quantum algorithms often assume independent spin qubits to produce trivial, mappings. This can be unrealistic in many solid-state implementations with sizeable magnetic interactions. Here we show that the lower part of the spectrum of a molecule containing three exchange-coupled metal ions with and is equivalent to nine electron-nuclear qubits. We derive the relation between spin states and qubit states in reasonable parameter ranges for the rare earth Tb 3+ and for the transition metal Cu 2+, and study the possibility to implement Shor's Quantum Error Correction code on such a molecule. We also discuss recently developed molecular systems that could be adequate from an experimental point of view.